Rancang Bangun Aplikasi Penerimaan Beasiswa Nahdlatul Ulama Scholarship (NUS) Oleh Lakpesdam PBNU : Design and Development of the Nahdlatul Ulama Scholarship (NUS) Admission Application by Lakpesdam PBNU - Rosyadi, Muhammad Bachtyar; Surya, Maulidina Rahmawati; Putri, Rismaya Nikmatul (Technomedia Journal, 2025)
The Nahdlatul Ulama Scholarship (NUS) is a program designed to improve access to higher education by providing financial support to outstanding students. This initiative is managed by the Institute for Human Resources Study and Development of the Nahdlatul Ulama Executive Board (LAKPESDAM PBNU), which aims to contribute to creating a more skilled and educated Indonesian population, in line with the national goal of improving the Human Development Index (IPM). Recognizing the importance of affordable and inclusive education, this program aims to support students with exceptional potential who are dedicated to achieving academic excellence. This research proposes the development of a web-based scholarship application using the CodeIgniter 4 framework and SQL database to streamline the scholarship acceptance process. The application is designed to provide easy access for both administrators and applicants, enabling efficient data management and simplifying the scholarship application process. The main goal of this application is to simplify the scholarship acceptance process, improve data management efficiency, and enhance the accessibility of the application system. The system will include features that facilitate online application submission, data validation, and real-time status updates. In conclusion, this application aims to support the goals of the NUS program by offering an accessible, user-friendly platform that meets the demand for quality education while improving operational efficiency. The development of this application is expected to contribute to broader efforts to achieve these objectives.